1980
DOI: 10.1016/0093-934x(80)90133-9
|View full text |Cite
|
Sign up to set email alerts
|

Reading between the lines: Event-related brain potentials during natural sentence processing*1

Abstract: Event-related potentials (ERPs) were recorded from subjects as they silently read 160 different seven-word sentences, presented one word at a time. Each sentence was in itself a natural, meaningful phrase. Substantial intersubject variability was observed in the ERP waveshapes following the words. More than half of the subjects generated P3 components to word stimuli, but those who did showed similar responses to repeated control presentations of a single word. In addition, it was found that all but the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
77
0
3

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(86 citation statements)
references
References 59 publications
6
77
0
3
Order By: Relevance
“…The novel ERP also was differentiated from that elicited by words presented in large type (Kutas and Hillyard, 1980b), both in its late negative and positive components. The ERP to the large words (third column FIGURE 1) did not contain any sharp, frontal component comparable to the N320.…”
Section: Discussionmentioning
confidence: 99%
“…The novel ERP also was differentiated from that elicited by words presented in large type (Kutas and Hillyard, 1980b), both in its late negative and positive components. The ERP to the large words (third column FIGURE 1) did not contain any sharp, frontal component comparable to the N320.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, the N400 effect was used to investigate semantic integration in language. For example, a greater N400 was observed when a word was semantically incongruent to the preceding sentence context (e.g., "socks" in "She spread her bread with socks") than when it was congruent ("butter" in "She spread her bread with butter"; Kutas & Hillyard, 1980, 1984. More recently, the N400 effect has also shown to be sensitive to integration of linguistic information with extralinguistic contexts (Hagoort, Hald, Bastiaansen, & Petersson, 2004;Van Berkum, Zwitserlood, Brown, & Hagoort, 2003) and to integration of pictorial information (West & Holcomb, 2002;Federmeyer & Kutas, 2001;McPherson & Holcomb, 1999;Ganis, Kutas, & Sereno, 1996;Barrett & Rugg, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…However, it goes beyond the findings in the literature by taking into account the variation in temporal synchrony and the inherent ambiguity of gesture in the absence of speech into account. Previous studies have shown that speech and gesture can be integrated into a stable (preexisting) and unambiguous context, similarly to how a visually presented word can be integrated into a preceding sentential context (Kutas & Hillyard, 1980). For example, they have shown that a word is integrated into a preceding gesture (Bernardis et al, 2008;Wu & Coulson, 2005;Kelly et al, 2004), that a gesture is integrated into the context created by a preceding sentence (Özyurek et al, 2007), and that a picture probe or a word was integrated with a preceding gesture-speech combination (Holle & Gunter, 2007;Wu & Coulson, 2007b).…”
mentioning
confidence: 99%
“…The LAN is a negative shift in the waveform, which is maximum around 400 ms after the presentation of an ungrammatical word. This is in a latency range similar to the N400 component (Kutas and Hilyard, 1980), which is elicited by semantic processing difficulties but it has a more anterior scalp distribution with a left hemisphere bias (Kluender and Kutas, 1993;Friederici et al, 1996). Scalp distribution, together with polarity, indicate whether two effects can or cannot be generated by the same population of neurons in the brain.…”
mentioning
confidence: 96%